Post-authorization safety studies of medicinal products : the PASS book - Ali, Ayad K.; Hartzema, Abraham G. (Academic Press, an imprint of Elsevier, 2018)
Post-Authorization Safety Studies of Medicinal Products: The PASS Book bridges the gap in the literature by providing a complete look at post-authorization safety studies and important pharmacoepidemiology and pharmacovigilance aspects. It covers various types and limitations of active surveillance programs, including the use of large databases and disparate data sources for rapid signal detection, as well as novel and advanced design and analysis approaches for causal interference from observational data. This book serves as an important reference for pharmacovigilance scientists and pharmacoepidemiologists who are searching for the appropriate study design to answer safety research questions. Readers will be able to effectively and efficiently design and interpret findings from post-authorization safety studies with the goal of improving the benefit-risk balance of a drug in order to optimize patient safety.